Serum Thyroid Hormone Levels During Peripartum Period In Osmanabadi Goat - Shinde, N.V.; Dalvi, S.H.; Gholave, C.S.; Kumarasamy , J. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Blood samples from eight Osmanabadi goats in their advance stage of pregnancy, aged between four to eight years were collected twice weekly and triiodothyronine (T3) and thyroxine (T4) were measured . The T3 concentration was ranged from 0.72 ± 0.03 to 1.13 ± 0.07 ng/ml during prepartum period and 1.02 ± 0.07 to 1.05 ± 0.07 ng/ml during postpartum period. The T4 levels ranged from 53.44 ± 5.4 to 69.98±2.84 ng/ml during prepartum period and 61.40 ± 4.50 to 79.30 ± 3.80 ng/ ml during postpartum period. Serum triiodothyronine (T3) was positively correlated with respiration rate, rectal temperature and fecundity rate. Triiodothyronine has shown significant positive correlation with pulse rate and rectal temperature while other relationships were statistically non significant.